Survey of the current distribution and status of bacterial blight and fungal diseases of cassava in Guinea - Bamkefa, B.A.; Bah, E.S.; Dixon, Alfred G.O. (2011)
A survey was carried out of 86 cassava fields in the lowland savanna; humid forest, mid-altitude savanna, and lowland humid savanna agroecological zones of Guinea. Each field was assessed for the incidence and severity of cassava bacterial blight (CBB), cassava anthracnose disease (CAD), Cercospora leaf blight (CLB), and brown leaf spot (BLS). Samples of diseased leaves were collected and used to identify associated pathogens. CBB was present in all the four major ecozones. The disease was observed in 88.88% of the fields visited in the humid forest. For other ecozones, results were 70.5% (mid-altitude savanna zone), 73.07% (lowland humid savanna), and 77.7% (low-land savanna). Anthracnose disease was observed in the humid forest and lowland humid savanna zones, but not in either of the others. CAD was observed in 11.11% of the fields visited in the humid forest, and in 19.23% in the lowland humid savanna. The disease was not observed in either of the others. CLB and BLS were observed in all the zones; however, the severity of both diseases was generally low and they did not seem to pose a serious threat to cassava tuberous root yield.